Tertiary Wastewater Treatment Using a Natural Peat Bog - Mechenich, David J. (University of Wisconsin-Stevens Point, College of Natural Resources, 1980)
The water quality of a sphagnum peat bog system at Drummond, WI was monitored at 39 sampling sites from October, 1977, to November, 1979, in order to characterize the natural water chemistry and to evaluate the bog's initial ability to assimilate secondarily treated domestic sewage. Routine water analyses included pH, conductivity, chloride, COD, BOD, ortho and total phosphorus, and ammonia, nitrate-nitrite, and Kjeldahl nitrogen. Fecal coliforms, total suspended solids, dissolved oxygen, metals, hardness, and alkalinity were occasionally measured. Background values were generally typical of a perched, ombrotrophic bog. Significant background variability occurred across the bog, with depth, and over time. From June through October, 1979, approximately 2.2 million gallons (8350 m^3) of wastewater were filtered through the bog. The wastewater was secondary lagoon effluent diluted with lake water used for initial lagoon filling and sealing. Effluent BOD5 and nitrogen were similar to the bog background. Effluent pH, chlorides, conductivity, alkalinity, hardness, phosphorus, and suspended solids were significantly higher, and COD was much lower. Analysis of water quality changes during the first 4.5 months of operation indicated an efficient assimilation of the effluent. Percent retention of nutrients from precipitation (1978) and precipitation plus effluent (1979) are listed below for the period from June through October. Significant reductions in effluent concentrations of chloride (60%), alkalinity (100%), hardness (83%), phosphorus (80%), and total suspended solids (95%), were also noted based on differences between the effluent and bog outflow water quality during the effluent discharge period. Effluent pH and conductivity were also significantly reduced, while COD increased 204%. Chloride tracing revealed that the effluent water primarily moved through the bog in the upper 0.5 meter. Other than chloride and conductivity increases, the most significant water quality changes within the bog appeared to be a drop in COD, BOD, phosphorus, and nitrogen below the established background levels at several well sites, and a reduction in background COD in the bog discharge. Leaching studies using Drummond peat cores were used to estimate the long-term potential of the bog to remove nutrients by physical-chemical processes. Under the specific experimental conditions, net phosphorus removals up to .191 mg P/gram oven dry weight peat were found, which was equivalent to approximately 40 kg P/acre-foot of surface peat soil. Nitrogen and calcium removals of .45 and 4.5.mg/gram oven dry weight peat respectively were also found.